General features and specific differences of the fuel-and-energy balances of European countries and Ukraine in the aspect of integrative tendencies in European energy sector - Novoseltsev A.V.; Kaplin M.I. (General Energy Institute of the National Academy of Sciences of Ukraine, 2008)
General problems, features and specific differences of the fuel-and-energy balances of European countries and Ukraine are analyzed in the aspect of integrative tendencies in European energy. The economic and math¬ematical model is developed for comparative analysis and optimization of the fuel-and-energy balances of European countries and Ukraine under integration processes in European energy sector.